Aplikasi Remote Sensing Untuk Analisis Geohidrologi Pada Area Sekitar Situs Tambang Intan Cempaka: Remote Sensing Application for Geohydrological Analysis in the Area Around the Cempaka Intan Mine Site - Ahmad Ali Syafi'i; Rudy Hendrawan Noor; Muh. Akram (LPPM Universitas Mataram, 2023)
Cempaka Diamond Panning is a location for traditionally processed diamond and gold panning located in Cempaka sub-district, Banjarbaru city, South Kalimantan. Mining activities cannot be separated from matters relating to the management of natural resources, which apart from providing benefits, there are also impacts or losses from these activities, especially for the environment. The diamond mine in Cempaka is included in the critical category which has the potential to flood when there is high intensity rain. Therefore, it is necessary to carry out geohydrological analysis using remote sensing. The method used is overlay and weighting by weighting spatial and non-spatial parameters in an area of 3189 Ha. From the results of the analysis, it is known that around 3057.61 Ha of the Cempaka region of interest (ROI) area is included in the flood-prone area and 75.88 Ha of the Cempaka region of interest (ROI) area is a slightly vulnerable area with information about three affected villages, namely Sungai Tiung, Bangkal and Cempaka.